2014
DOI: 10.1002/adfm.201304114
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐Insensitive Amorphous Oxide Thin‐Film Transistor Integrated with a Plasmonic Filter for Transparent Electronics

Abstract: 3482www.MaterialsViews.com wileyonlinelibrary.com gate bias stress during most of the driving time and transparent devices are exposed to ambient light unavoidably. The stability resulting from electrical stress under light illumination is important since it can deteriorate the switching performances of a-IGZO-based TFTs. It was found that the positive bias illumination stress is insignifi cant compared to the negative bias illumination stress (NBIS). [ 7 ] NBIS has been explained by photo-induced carriers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Equally important, the high optical transparency of MO semiconductors can enable fully transparent thin‐film transistors (TFTs), which are essential for the fabrication of “invisible” circuits and to increase the aperture ratio of active‐matrix organic light‐emitting diode (AMOLED) and liquid‐crystal (LC) displays . Therefore, since the first report of a fully transparent MO‐based TFT in 2003, extensive academic and industrial efforts have focused on enhancing device performance for both opaque and transparent applications . Nevertheless, the best performing MO TFTs are typically fabricated by capital‐intensive physical and chemical vapor deposition processes.…”
Section: Performance Metrics For Mo:pvp Tfts With Different Concentramentioning
confidence: 99%
“…Equally important, the high optical transparency of MO semiconductors can enable fully transparent thin‐film transistors (TFTs), which are essential for the fabrication of “invisible” circuits and to increase the aperture ratio of active‐matrix organic light‐emitting diode (AMOLED) and liquid‐crystal (LC) displays . Therefore, since the first report of a fully transparent MO‐based TFT in 2003, extensive academic and industrial efforts have focused on enhancing device performance for both opaque and transparent applications . Nevertheless, the best performing MO TFTs are typically fabricated by capital‐intensive physical and chemical vapor deposition processes.…”
Section: Performance Metrics For Mo:pvp Tfts With Different Concentramentioning
confidence: 99%
“…In this way, periodic hole structure show better filtering characteristics such as high transmission and good color selectivity. We previously reported on MNA-based chromatic filters, including their design method and integration on realistic devices; 12 the fabrication method for large area applications; 13 and an MNA-based plasmonic filter integrated on transparent TFTs, which had the effect of improving the instability of TFTs under light 14 .…”
Section: Introductionmentioning
confidence: 99%
“…4,10 In addition, a-IGZO TFTs are susceptible to atmosphere such as oxygen and moisture, 24,25 and have problems in long-term stability 24 for which the mechanism is not yet clear and under debate for years. 26 Therefore, we recently proposed an alternative idea on development of In-Si-O (ISO) 7,8 and In-W-O (IWO) 10,11 transistors in which the doped acidic oxides have much stronger bond dissociation energy and are more rigid to acid, and found that the doped amorphous TFTs inert to oxygen remained electrically stable even without any passivation layer which can reduce production cost.…”
Section: Controllable Film Densification and Interface Flatness For Hmentioning
confidence: 99%